Innovation of Cognitive Diagnostic Assessment in Mahārah istimā’ in Class XII Arabic Textbook - Resgi Widati Tria Lis Utami; R. Umi Baroroh; Nur Yusra Binti Yacob (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This research aimed to create an assessment innovation in the form of a cognitive diagnostic assessment that is in accordance with the language skills that should be possessed by class XII of high school students. This study used a qualitative descriptive research method. The results of this study show that cognitive diagnostic assessment in Mahārah istimā’ consists of 10 questions. 2 questions are taken from the subject matter that has been studied in the two classes below in semester 2. 6 questions are from the subject matter in 1 class below in semesters 1 and 2. And 2 questions are from the subject matter to be studied. Types of tests are divided into objective and subjective tests. The objective test used is a multiple-choice, true-false test, and completes a brief description of the various questions heard by the teaching teacher. Meanwhile, the subjective test used is to complete the answers to the questions heard both in the form of discourse and dialogue in long descriptions.